1998
DOI: 10.1165/ajrcmb.18.5.3030
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IgE Heavy Chain Transcripts in the Sinus Mucosa of Atopic and Nonatopic Patients with Chronic Sinusitis

Abstract: We have recently shown the increased mRNA expression of interleukin (IL)-4 and IL-13 in sinus biopsies from allergic subjects with chronic sinusitis (ACS), whereas only IL-13 mRNA was elevated in biopsies obtained from nonallergic subjects with chronic sinusitis (NCS). In the lymph nodes and spleen, these cytokines may promote IgE production through transcriptional activation of the germline IgE heavy chain promoter, an event which precedes immunoglobulin isotype switching to IgE in B cells. We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…The IgE self-sufficiency of the nasal mucosa may also explain how many individuals diagnosed as nonatopic, based on skin prick tests and low serum IgE levels, nevertheless manifest allergy-like symptoms. Indeed, elevated levels of ⑀ GL transcripts and mature ⑀ mRNA have been observed within the ethmoid sinus and the lung even in individuals diagnosed with nonatopic sinusitis and asthma (23,24). Interestingly, these data parallel observations of IgA isotype switching within the gut lamina propria (38), suggesting that local synthesis of Igs may be a property of peripheral tissues strategically located at the site of Ag entry.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The IgE self-sufficiency of the nasal mucosa may also explain how many individuals diagnosed as nonatopic, based on skin prick tests and low serum IgE levels, nevertheless manifest allergy-like symptoms. Indeed, elevated levels of ⑀ GL transcripts and mature ⑀ mRNA have been observed within the ethmoid sinus and the lung even in individuals diagnosed with nonatopic sinusitis and asthma (23,24). Interestingly, these data parallel observations of IgA isotype switching within the gut lamina propria (38), suggesting that local synthesis of Igs may be a property of peripheral tissues strategically located at the site of Ag entry.…”
Section: Discussionmentioning
confidence: 56%
“…Although isotype switching has classically been considered an event restricted to germinal centers within lymph nodes and spleen, ⑀ GL transcripts have been observed within nasal (22), ethmoidal (23), and bronchial (24) biopsies of individuals with rhinitis, sinusitis, and asthma following in vivo allergen exposure. Furthermore, the nasal mucosa from individuals with allergic rhinitis produces ⑀ GL transcripts following ex vivo allergen challenge (25).…”
mentioning
confidence: 99%
“…In 1998, Ghaffar et al, while studying individuals with chronic rhinosinusitis (CRS) with and without evidence of atopic disease on SPT, determined by immunocytochemistry of the nasal mucosa that the B cell population was significantly higher in the atopic CRS group [11]. In this study, in situ hybridization was used to analyze mRNA transcripts as an early indicator of class switching to IgE in B cells, which were found to be elevated in both atopic and non-atopic CRS individuals, compared to that in healthy controls, though significantly higher in atopic individuals.…”
Section: Regions Where Local Ige Is Present Upper Aerodigestive Tractmentioning
confidence: 99%
“…Likewise, levels of IgE in the serum may need to also reach a threshold before they can be transported to a predetermined local region. Studies have demonstrated that local IgE in the sinonasal mucosa is more likely to be detected when total IgE levels in the serum are elevated or if the SPT grade is higher [7,11,47 •• ]. Currently, the signals which are orchestrating this complex transit system for antigen-specific IgE are largely unknown.…”
Section: Immunotherapy Without Systemic Evidence Of Atopy?mentioning
confidence: 99%
“…It has been suggested that prior work evidencing local IgE synthesis in nasal tissue is applicable to the pulmonary system as well. 8,76,77 ANTIGEN SPECIFICITY OR DISORDERED PRODUCTION?…”
Section: Local Ige: Pulmonarymentioning
confidence: 99%